EFFECTS OF RUNNING ON RECOVERY OF FUNCTION IN ATHLETES WITH KNEE OSTEOARTHRITIS - Huang,Jianwu (2022)
ABSTRACT Introduction Running can promote health prevent obesity, cardiovascular, and cerebrovascular diseases, among other chronic diseases. Much research reports the benefits of this aerobic resistance exercise, but little is known about the impacts of running on knee osteoarthritis. Objective To observe and study the clinical effect of running on pain and function improvement in patients with knee osteoarthritis. Methods Seventy cases that met the inclusion criteria were selected and randomly divided into control and observation groups. Patients in the observation group received eight weeks of neuromuscular exercise (NEMEX) and eight weeks of quadriceps muscle strength training while the control group was subjected to a running protocol. Patients were assessed using the Western Ontario and McMaster Universities Pain Scale and Osteoarthritis Index (WOMAC) after 1, 2, 4 and 8 weeks of treatment. Results After 1, 2, 4, and 8 weeks of treatment, the WOMAC function scores of the two groups significantly improved compared to that found before treatment (P < 0.05); There was no difference between the two groups before treatment and after 1, 2 weeks of treatment. After 4 and 8 weeks of treatment, the function of the observation group was better than that of the control group; the difference was statistically significant (t= -4.287, -6.355, P<0.05). Conclusions NEMEX training methods and quadriceps muscle strength training can effectively improve patients’ functional level, but NEMEX improves more significantly than quadriceps muscle strength training. Evidence level II; Therapeutic Studies - Investigating the results.